Enhancement of Depleted Loam Soil as Well as Cucumber Productivity Utilizing Biochar Under Water Stress. Issue 1 (2nd January 2019) - Ali, Abubaker, B.; Haofang, Yan; Hong, Li; Yan You, Wu; Elshaikh, Nazar A.; Hussein, Gameraldawla; Pandab, Sudhindra; Hassan, Sami
ABSTRACT: Biochar has recently received increased attention because it improves poor soil fertility. However, its potentiality to enhance soil physical properties under water stress conditions not yet deeply investigated. Hence, extensive field investigations were carried out to study the effects of biochar addition (BA) with deficit irrigation (DI) on soil bulk density (BD), porosity percentage (P%), soil moisture content (SMC%), soil hydraulic conductivity (K), cucumber yield and water use efficiency (WUE) during two consecutive seasons (2016 and 2017). The biochar treatments were B0 (0 ton ha −1 ), B1 (10 ton ha −1 and B2 (20 ton ha −1 ), while the DI treatments were 1.0 (W1 ), 0.60 (W2 ) and 0.40 (W3 ) of the reference evapotranspiration (ET0 ). The parameters were measured at soil depths of 0–10 (d1 ), 10–20 (d2 ) and 20–30 cm (d3 ) for measurement periods of before sowing (P1 ), mid-season (P2 ) and after harvest (P3 ). The results showed that the B2 W1 combination gave the highest yield (57 and 45.2 t ha −1 ), WUE (10.94 and 11.27 kg m −3 ), SMC (39.2 and 40.1%) in both seasons, respectively. The B2 W3 had the highest porosity (47.5 and 46.1%) values at the d1 . Meanwhile, the lowest soil BD values of 1.1 and 1.05 g cm −3 were obtained by the B2 W1 at d1 for 2.16 and 2017, respectively. Statistically, most of the parameters studied under B2 W2 and B0 W1 had non-significant differences between them. Hence, the addition of biochar with DI could be an integrated approach to address the drought stress, while enhancing soil and plant properties.